Acute Toxicity Test of Healthy Drink of Anthocyanin Pigmented Polyphenols from Black Rice and Sprouts Soybean - Kintoko Kintoko; Nina Salamah; Hardi Astuti Witasari; Rizlah Maulizah (Journal of Food and Pharmaceutical Sciences, 2026)
Black rice and sprouted soybean (BRiSS) can be formulated into a healthy drink BRiSS. The safety of this novel combination must be rigorously tested. Therefore, this study was designed to conduct a comprehensive acute toxicity test of the healthy drink flavylium anthocyanins from black rice (Oryza sativa L. indica) pigmented polyphenols from soybean sprouts (Glycine max L.). The black rice was extracted with a 96% ethanol solution in 3% citric acid. The pigmentation process was achieved by adding hydroxyl groups from soybean polyphenols. The active material was mixed with 20% maltodextrin, shaken, poured into a pan, and dried with a cabinet dryer (60° C). The mixture was stirred with 0.3% sodium, 0.1% citric acid, 50% active ingredients, 5% sucrose as a sweetener, 0.05% sodium benzoate, and water, 100 ml. The five groups of male Wistar rats were acclimatized. Group 1 was a control, and groups 2, 3, 4, and 5 were sequentially treated with a healthy drink containing extract doses of 5, 50, 300, and 2000 mg/kg BW. The acute toxicity test results at 30 minutes, 3 to 24 hours, day 3, and day 14 were written on the acute toxicity test clinical symptom observation sheet. All test animals, including both the control and test groups with various dosage variations, did not exhibit changes in skin, fur, eyes, behavior, respiratory systems, and did not experience weight loss, seizures, tremors, lethargy, or diarrhea. The limitation was that the macropathology examination of internal organs (kidneys, liver, heart, brain, stomach, intestines, pancreas) was not performed. Not all animals have mortality in a 5-3000 (mg/kg BW) extract dose.